This was not the plan [large type] - Alger, Cristina (Thorndike Press large print core series., 2016)
From the acclaimed author of The Darlings comes an incisive, hilarious, heartbreaking and tender exploration of fatherhood, love, and family life through the story of a widower who attempts to become the father he didn't know he could be.